Temporal evolution of relationships between temperature and circulation modes in five reanalyses. (16th December 2021) - Hynčica, Martin; Huth, Radan
Abstract: Temporal evolution of relationships between surface temperature and modes of low‐frequency circulation variability is compared between five reanalyses (20CRv3, 20CRv2c, ERA‐20C, JRA‐55, and NCEP‐1) in winter from 1958 to 2010 over the northern Extratropics. The relationships are evaluated using 15‐year running correlations between temperature anomalies (from the CRU TS v. 4.03 data set) and the intensity of circulation modes (detected in 500 hPa heights by rotated principal component analysis). The analysis, utilizing mean absolute differences between time series of running correlations, points to the large agreement between ERA‐20C, JRA‐55, and NCEP‐1. Circulation modes in those reanalyses are highly similar, which in turn lead to the agreement in temporal development of correlations. In contrast, relationships of some circulation modes with temperature in 20CRv3 and 20CRv2c differ due to differences in the position, strength, and shape of the action centres. This concerns circulation modes located over Eurasia and the Atlantic, mainly North Atlantic Oscillation and Eurasian mode type 1 (EU1). Composite maps, calculated for all running periods, indicate dissimilar temporal evolution of action centres in both 20CR reanalyses. Increased differences in correlations occur mainly during periods when the position and strength of action centres diverge the most. Relationships of circulation modes located over North America and the Pacific with temperature share large resemblance between all reanalyses, including those from the 20CR family. Differences appear to be smaller in 20CRv3 compared to the preceding version, 20CRv2(c), suggesting that the development of the 20CR reanalysis has succeeded in correcting and diminishing biases. Abstract : Temporal evolution (defined by running correlations) of relationships between temperature and circulation modes is compared between five reanalyses from 1958 to 2010. The large spatial similarity of modes between reanalyses leads to similar running correlations; this concerns the JRA‐55, NCEP‐1, and ERA‐20C reanalyses. In the 20CRv2c and 20CRv3 reanalyses, relationships with circulation modes located over Eurasia and the Atlantic, mainly North Atlantic Oscillation and Eurasian mode type 1, evolve differently due to differences in the position, strength, and shape of the action centres.